Adsorption of copper(II) and lead(II) ions by palm kernel shell-derived activated carbon - Isokise, Ekemini Monday (2019)
In the wastewater treatment plant, activated carbon is a widely used adsorbent to remove heavy metals and organic pollutants, but it is very expensive. Therefore, adsorption by utilizing different types of agro-residues is one of the alternative materials to remove various contaminant from solutions. Due to the high toxicity of Pb and Cu as trace metal pollutants in the environment, many studies have dedicated to suggest possible ways of eliminating these metals from the environment. This study focus on preparation of activated carbon from Palm Kernel Shell as economically and environmental friendly adsorbent for removal of Pb²⁺ and Cu²⁺ from aqueous solution. The activated carbon prepared were mainly mesoporous in nature with BET surface area and isoelectric point (IEP) ranged from 1004 to 1083 m²/g and 2.8 to 3.1, respectively. Effect of operating parameters such as activated carbon dosage, contact time, temperature, metal ion concentration and pH were investigated. Adsorption capacity was found to vary with initial concentration, adsorbent dose and pH. An increase in pH led to a significant increase in heavy metal removal suggesting the involvement of ion exchange mechanism. Adsorption kinetics, isotherms and thermodynamics parameters of the metal ions sorption process were also evaluated. Pseudo-second-order kinetics explained the adsorption process satisfactorily, which suggests chemisorption as the rate limiting step and mechanism for the removal of Cu²⁺ and Pb²⁺. The Langmuir isotherm model was most suitable for describing the adsorption process. The monolayer saturated adsorption capacities of AC-600 2:1(4) for Pb²⁺ and Cu²⁺ was 114.9 mg/g and 27.93 mg/g, respectively. Therefore, the prepared palm kernel shell based activated carbon found to be efficient in removing heavy metal.